Evaluation of Pharmacy Management Information System with Hot-Fit Method at Dr Yap Eye Hospital Yogyakarta - Justika Susane Antahari (International Journal of Healthcare Research, 2019)
Pharmacy Management Information System (SIMP) is an information system used by Dr. Yap Eye Hospital Yogyakarta which aims to handle management processes related to data and information on hospital pharmacy services. The implementation of SIMF is currently experiencing several problems, namely from the use of the system and the system itself. This study aims to evaluate the implementation of the Pharmacy Management Information System (SIMP) using the HOT-Fit method at Dr. Yap Eye Hospital Yogyakarta. This type of research is a mix method with an explanatory sequential design. The sample in this quantitative study amounted to 105 respondents who were determined by proportionate random sampling technique. While the qualitative sample of 5 informants was determined by purposive sampling technique. The instruments used include questionnaires and interview guides. Quantitative analysis was carried out with Microsoft Excel in 2016 and qualitative analysis was carried out manually using a computer. Based on the results of quantitative-qualitative, the human aspect: system users (95%) are already good because the system is used routinely and training is carried out and user satisfaction (90%) is satisfied because the system helps the work of staff. Organizational aspect (98%) is good because of the support from top management. Technology aspect: system quality (96%) is good because the system is easy to use, information quality (92%) is good because the information produced is complete and time, and service quality (91%) is already good because of the support from the hospital IT. The benefit aspect (100%) has helped to improve the efficiency and effectiveness of staff at work. Evaluation of SIMF implementation at Dr. Yap Eye Hospital Yogyakarta in the aspects of human, organization, technology and benefits has been going well.